The effectiveness of a training program in enhancing teachers' awareness of the foundations of differentiated instruction for gifted students with ASD (The International Journal for Scientific Research, 2025)
The study aimed to reveal the effectiveness of a training program in enhancing teachers' awareness of the foundations of differentiated instruction for gifted students with autism spectrum disorder. To achieve the study's objectives, the researchers adopted a quasi-experimental approach, which involved investigating the effectiveness of the training program in enhancing teachers' awareness. The researchers used a quasi-experimental design with pre- and post-tests for a single group, and a descriptive approach, which involved researching the information collected by reviewing previous literature and studies. The study sample consisted of (30) teachers in the kindergarten and primary stages at the Abdul Latif Al-Fawzan Center for Autism in Al-Khobar. The study was conducted during the first semester of the year 1447 AH. The instruments included a proposed training program (prepared by the researchers) and a questionnaire to measure the impact of the training program (prepared by the researchers), which was administered to the sample before and after the program's implementation in order to extract differences and determine the degree of effectiveness of the training program in enhancing awareness among the sample members in the pre- and post-tests. The results answered the study's main question, confirming the effectiveness of the training program in enhancing teachers' awareness of the principles of differentiated instruction for gifted students with autism spectrum disorder. This was demonstrated by a significant increase in the sample's average post-test scores compared to the pre-test, indicating the program's effectiveness. The study recommended expanding the training program to include as many teachers of gifted students with autism spectrum disorder as possible.
Keywords: Effectiveness; Awareness Enhancement; Differentiated Instruction; Gifted Students; Autism Spectrum Disorder